Cholestatic liver diseases of genetic etiology: Advances and controversies. Issue 6 (17th March 2022) - Ibrahim, Samar H.; Kamath, Binita M.; Loomes, Kathleen M.; Karpen, Saul J.
Abstract: With the application of modern investigative technologies, cholestatic liver diseases of genetic etiology are increasingly identified as the root cause of previously designated "idiopathic" adult and pediatric liver diseases. Here, we review advances in the field enhanced by a deeper understanding of the phenotypes associated with specific gene defects that lead to cholestatic liver diseases. There are evolving areas for clinicians in the current era specifically regarding the role for biopsy and opportunities for a "sequencing first" approach. Risk stratification based on the severity of the genetic defect holds promise to guide the decision to pursue primary liver transplantation versus medical therapy or nontransplant surgery, as well as early screening for HCC. In the present era, the expanding toolbox of recently approved therapies for hepatologists has real potential to help many of our patients with genetic causes of cholestasis. In addition, there are promising agents under study in the pipeline. Relevant to the current era, there are still gaps in knowledge of causation and pathogenesis and lack of fully accepted biomarkers of disease progression and pruritus. We discuss strategies to overcome the challenges of genotype–phenotype correlation and draw attention to the extrahepatic manifestations of these diseases. Finally, with attention to identifying causes and treatments of genetic cholestatic disorders, we anticipate a vibrant future of this dynamic field which builds upon current and future therapies, real‐world evaluations of individual and combined therapeutics, and the potential incorporation of effective gene editing and gene additive technologies.